Transfusion-dependent b-Thalassemia Major Bangladeshi Child Treated Successfully with Combination of Hydroxyurea and Low- Dose Thalidomide : A Case Report (Bangladesh Journal of Child Health, 2024)
Beta thalassemia results from absent or reduced production of beta globin gene leading to excess of alpha chain which causes ineffective erythropoiesis and marked anemia. b-thalassemia major patients usually present early within 2 years of life mostly in 2nd six months of first year of life. Only curative treatment till date is bone marrow transplantation. However, it is not feasible for all because of rarity of matched donar and obviously for its high cost and unavailability of services particularly in a developing country like Bangladesh. Hence regular blood transfusion remain the ultimate choice of their survival, growth and development with the cost of iron overload in the resource constraints country like ours. Recently HbF inducing drugs are showing promising result in the management of thalassemia children by inducing fetal hemoglobin. However, data are scarse from Bangladesh.Here we are reporting a case of betathalassemia who was diagnosed at 18 months of age and treated with only blood transfusion upto 2 years then hydroxyurea was given for 12 months with no response and then she was kept on regular blood transfusion with iron chelation up to 6 years with regression splenic size to normal and to maintain normal growth and development. After then she was given hydronix plus thalidomide in combination and responded well and remained transfusion free for last 3 years.Bangladesh J Child Health 2023; Vol 47 (2) : 117-120